Speaking in Public About Science: A Quick Guide for the Preparation of Good Lectures, Seminars, and Scientific Presentations - Albuquerque, Ulysses Paulino de (Springer, 2016)
This book introduces the basic techniques and methods traditionally used in speaking about science to the public. The public often has a very different perception and understanding of science, and this must be taken into account when communicating with the public. This volume covers methods of scientific discourse, oral communication, preparation of the presentation, techniques and use of visual resources, and exercises for perfecting the technique of speaking in public about science.